Assessment of the Health Status of Women in Prison: A Comparison between Drug Users versus Non-users - Alves, Joana (International journal of offender therapy and comparative criminology, 2023)
This study aims to analyze the history of substances use, clinical diagnoses, contacts with healthcare, and health complaints. Also, it aims to compare the health status of substance users versus non-users. Health records of 93 detained women from a prison in northern Portugal, with a mean age of 38.02 years old, were reviewed and coded using both International Classification of Primary Care—2 and International Classification of Diseases—10th. Data revealed high percentages of detainees with a history of substance use and pre-existing clinical diagnosis. During the first month of imprisonment, on average, participants had complained to a health professional 14.63 times. Substance users were younger and presented more mental health problems and health complaints. Health policies and professional practices in prison must include immediate assessment of a woman’s health concerns and foster the development of efficient protocols to address those problems, especially substance use disorder treatment.